Paradoxical heat sensation as a manifestation of thermal hypesthesia: a study of 1090 patients with lesions of the somatosensory system - Vollert, Jan; Fardo, Francesca; Attal, Nadine; Baron, Ralf; Bouhassira, Didier; Enax-Krumova, Elena K.; Freynhagen, Rainer; Hansson, Per; Jensen, Troels S.; Kersebaum, Dilara; Maier, Christoph; Pogatzki-Zahn, Esther; et al. (Pain, 2024)
Paradoxical heat sensation (PHS) is the perception of warmth when the skin is cooled. Paradoxical heat sensation rarely occurs in healthy individuals but more frequently in patients suffering from lesions or disease of the peripheral or central nervous system. To further understand mechanisms and epidemiology of PHS, we evaluated the occurrence of PHS in relation to disease aetiology, pain levels, quantitative sensory testing parameters, and Neuropathic Pain Symptom Inventory (NPSI) items in patients with nervous system lesions. Data of 1090 patients, including NPSI scores from 404 patients, were included in the analysis. We tested 11 quantitative sensory testing parameters for thermal and mechanical detection and pain thresholds, and 10 NPSI items in a multivariate generalised linear model with PHS, aetiology, and pain (yes or no) as fixed effects. In total, 30% of the neuropathic patients reported PHS in contrast to 2% of healthy individuals. The frequency of PHS was not linked to the presence or intensity of pain. Paradoxical heat sensation was more frequent in patients living with polyneuropathy compared with central or unilateral peripheral nerve lesions. Patients who reported PHS demonstrated significantly lower sensitivity to thermal perception, with lower sensitivity to normally painful heat and cold stimuli. Neuropathic Pain Symptom Inventory scores were lower for burning and electric shock-like pain quality for patients with PHS. Our findings suggest that PHS is associated with loss of small thermosensory fibre function normally involved in cold and warm perception. Clinically, presence of PHS could help screening for loss of small fibre function as it is straightforward to measure or self-reported by patients.